(untitled) (Acta Scientiarum. Animal Sciences, 2017)
The objective of this study was to characterize the beef cattle farming profile in the State of Piauí for inference about the zootechnical record of animals for insertion into a traceability system. Data were collected through a semi-structured multiple choice questionnaire applied to 400 cattle breeders in all microregions of the state, in May and November 2012. The questions contained the following indicators: profile of the property and the breeder, herd conditions and technical conditions on herd registration. The cattle-raising scenario is predominantly characterized by family activity, with the majority of producers over 50 years of age, who are without great prospects for technological innovation, inserted in an environment where human resource renewal faces difficulties. Data analysis verified the prevalence of herds with up to 50 cattle farmed on properties with up to 50 ha, without individual identification of the animals. These results, coupled with the fact that the cattle breeders are technically unaware of the importance of the zootechnical record and the traceability, indicate the low probability of the activity to be inserted in a computerized environment.